Speed structure of the mantle under the Dnieper-Donets depression and its surrooudings. Pt. II - T. A. Tsvetkova; I. V. Bugaenko; L. N. Zaets (Геофизический журнал, 2020)
This work is a continuation of the analysis of the velocity structure of the mantle beneath the Dnieper-Donets Basin and its environment, which includes the north of the Ukrainian Shield and the south of the Voronezh crystalline massif (based on the three-dimensional P-velocity model of the mantle). According to geological data, the Dnieper-Donets Basin consists of 4 parts. According to the P-speed model, the mantle beneath the Dnieper-Donets Basin is divided into 2 parts: the first part corresponds to the Chernihiv and Lokhvitsa segments, the second one includes the Izyum and Donets segments. Influence is noted on the first part of Volyn-Orsha, on the second one of the North-Azovian plume. Super deep fluids are identified that affect the characteristics of the Dnieper-Donets depression. The Izyum segment corresponds to the southern end of the Kursk-Belgorod fluid (fluid f4) and the northern end of the fluids f3 and f12. The Lokhvitsa segment includes the northwestern part of the fluid f3, as well as the northwestern end of the fluid f2, and the southwestern end of the fluid f4. The northeastern end of fluid f2 refers to the Chernigov segment, the northeastern end of fluid f12 refers to the Donbas segment. The earthquakes of the region in question additionally confirm its division into the Chernigov, Lokhvitsa, Izyum and Donets segments. An analysis is made of the change in the velocity gradient with depth for a given region, which allows to determine the seismic boundaries of the mantle (the inflection points of the gradients of the velocity curves correspond to the velocity boundaries). Based on them, the depth of the main geodynamic boundary of the mantle (the bottom of the transition zone of the upper mantle) is identified. Under the Lokhvitsa, Izyum and Donets segments of the Dnieper-Donets Depression, it is defined as 625 km. A depth of 575 km is characterized by a large part of the Chernigov segment and the northwestern part of the Izyum segment, corresponding to the Kursk-Belgorod fluid. Such a depth of the main geodynamic boundary of the mantle corresponds to degassing processes. Changing the velocity gradients with depth once again draws attention to the division of the studied area into two parts. In the eastern part, to which the Izyum and Donets segments belong, a zone of subcrustal waveguides stands out. For the Chernigov and Lokhvitsa segments, subcrustal waveguides are not distinguished, with the exception of the extreme northeast of the Lokhvitsa segment, where the Kursk-Belgorod fluid region extends. The explanation of the observed structure of the eastern part of the upper mantle (Izyum and Donets segments) is based on the assumption that the formation of waveguides in it is associated with an uneven rise to the surface of super deep fluids.